Impacts of chemistry in executive coaching - Perkins, Janice (My University, 2026)
In executive coaching, the initial "chemistry test" between coach and client is widely acknowledged as a pivotal determinant of coaching effectiveness. This process assesses relational fit, and trust to shape the potential for depth, openness, and constructive challenges within the coaching relationship. While often described as “clicking,” synchronicity, or rapport, the phenomenon of chemistry remains underexplored in coaching scholarship despite its apparent influence on coaching outcomes and team dynamics. Drawing on my experiences in athletics, corporate training, and executive coaching, this study investigated chemistry as both an interpersonal attraction and a dynamic process of coherence. In athletic contexts, chemistry on the court demonstrates its power to create momentum and cohesion, while in corporate environments, neglecting chemistry in favor of skills and productivity limit team performance and growth. As a coach, I observe how chemistry accelerates trust-building, deepens dialogue, and fosters stronger outcomes, not only between coach and client but also within the teams they lead. For this dissertation, chemistry is conceptualized as a strong mutual attraction or interaction between individuals, characterized by trust, rapport, genuineness, and positive bonds (Passarelli et al., 2023). Related constructs such as resonance, entrainment, and entwinement describe the rhythmic alignment that emerges when two systems interact in synchrony (Clayton, 2012; Sandra & Nandram, 2013, 2020). Extending beyond the dyadic coaching relationship, the study also considers coherence—the synchronization of rhythms over time that cultivates connectedness, alignment, and unity of purpose across teams and organizations (Sandra, 2022). The purpose of this hermeneutic phenomenological study was to explore the influence of chemistry moments within coaching relationships on the coachee, their immediate team, the broader organization, and potentially on extended communities. Secondly, to look at whether the emergence of chemistry can be maintained or if it transfers creating coherence in teams, companies, cultures and communities. The qualitative research data was collected via zoom of three session each of six coaching pairs. These sessions were recorded and transcribed. Those recordings were viewed and the transcripts read for guidance with choosing the video elicitation clips. All the participants were interviewed once then a second time after watching video elicitations. The data revealed chemistry as a co-created, practice-based relational phenomenon rather than a function of rapport, personality fit, or emotional closeness. Across coaching pairs, chemistry emerged through inquiry, disruption, coordinated rhythm, and shared meaning-making, often intensifying in moments of adaptive tension. It operated asymmetrically, could be carried by one party, and functioned across multiple layers, producing identity stabilization, agency activation, and portable leadership impact. Chemistry was shown to accelerate insight and extend beyond the coaching pair into adjacent relationships and systems. Positioned alongside Social Penetration Theory, Ubuntu-informed Collective Leadership Theory, and Leadership-as-Practice, chemistry emerged as an enabling relational field condition, rather than a byproduct of closeness.
Keywords: Chemistry; Entrainment; Coherence; Entwinement; Ubuntu; Syncing; Collective; Leadership as practice